Non-deacetylated poly-N-acetylglucosamine-hyperproducing Staphylococcus aureus undergoes immediate autoaggregation upon vortexing - Kutsuno, Shoko; Hayashi, Ikue; Yu, Liansheng; Yamada, Sakuo; Hisatsune, Junzo; Sugai, Motoyuki (Frontiers in Microbiology, 2023)
Biofilms are microbial communities of cells embedded in a matrix of extracellular polymeric substances generated and adhering to each other or to a surface. Cell aggregates formed in the absence of a surface and floating pellicles that form biofilms at the air-liquid interface are also considered to be a type of biofilm. Staphylococcus aureus is a well-known cause of biofilm infections and high-molecular-weight polysaccharides, poly-N-acetylglucosamine (PNAG) is a main constituent of the biofilm. An icaADBC operon comprises major machinery to synthesize and extracellularly secrete PNAG. Extracellular PNAG is partially deacetylated by IcaB deacetylase, and the positively charged PNAG hence interacts with negatively charged cell surface to form the major component of biofilm. We previously reported a new regulator of biofilm (Rob) and demonstrated that Rob binds to a unique 5-bp motif, TATTT, present in intergenic region between icaADBC operon and its repressor gene icaR in Yu et al. The deletion of the 5-bp motif induces excessive adherent biofilm formation. The real function of the 5-bp motif is still unknown. In an attempt to isolate the 5-bp motif deletion mutant, we isolated several non-adherent mutants. They grew normally in turbid broth shaking culture but immediately auto-aggregated upon weak vortexing and sedimented as a lump resulting in a clear supernatant. Whole genome sequencing of the mutants identified they all carried mutations in icaB in addition to deletion of the 5-bp motif. Purification and molecular characterization of auto-aggregating factor in the culture supernatant of the mutant identified that the factor was a massively produced non-deacetylated PNAG. Therefore, we created a double deficient strain of biofilm inhibitory factors (5-bp motif, icaR, rob) and icaB to confirm the aggregation phenomenon. This peculiar phenomenon was only observed in Δ5bpΔicaB double mutant but not in ΔicaR ΔicaB or ΔrobΔicaB mutant. This study explains large amount of extracellularly produced non-deacetylated PNAG by Δ5bpΔicaB double mutation induced rapid auto-aggregation of S. aureus cells by vortexing. This phenomenon indicated that Staphylococcus aureus may form biofilms that do not adhere to solid surfaces and we propose this as a new mechanism of non-adherent biofilm formation of S. aureus.